ANALISIS HADIS-HADIS TENTANG BERDOA - Dame Siregar (IAIN Padangsidimpuan, 2018)
Pray religious service which do not be locked out of by good human life of moment like or is hard. Pray at the same time take care a[n without exception compulsion. Follow existing prayer in Alquran and of hadis good in solat and outside solat. Pray better alone and slow or sir. Way of praying better without hands up and sweep face with palm have prayed. Comand of have religious service to ought to look for theorem govern and way of practicing him it. If not yet earned better don't is first practiced. Doing a good deed us by owning strong theorem. Daalam religious service of solat janazah represent religious service of terkhir to it directly non jahar and [do] not hands up, hence him [there] no term of masbuq in janazah solat.